Sacred Flames in Text: Semiotic Interpretation of the Sacrificial Fire Symbolism in Rāmāyaṇa Djawa-Kuna - Setyani , Turita Indah; Idayanti , Iik; Sunengko, Sunengko; Sakka, Wahyuni (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2025)
The Rāmāyaṇa has long been recognized as one of the most influential epics that bridges literature, spirituality, and cultural philosophy across Asia, yet studies on its Old Javanese version have tended to focus primarily on textual form, metrical beauty, or general philosophical themes while neglecting the symbolic evolution of elemental motifs. This study addresses that gap by applying Roland Barthes’s semiotic theory in conjunction with Hindu religious perspectives to interpret the evolving role of sacrificial fire across four key episodes. A literary-religious analysis was conducted using Poerbatjaraka’s authoritative edition as the primary source, complemented with secondary studies on Hindu ritual fire traditions. The results show that fire undergoes a sequential transformation: it first manifests as emotional turmoil reflecting grief and instability, then becomes a solemn witness to alliances and loyalty, later functions as a purifier and defiant judge against deceit, and finally culminates as the sacred medium of self-sacrifice and the cosmic union of Atman and Brahman symbolized in Ardhanareswara. These findings demonstrate that fire in the Rāmāyaṇa Djawa-Kuna is not a static emblem but a dynamic symbolic agent that shapes psychological states, validates social bonds, and mediates transcendental union. By mapping these shifting connotations, the study contributes to literary scholarship by offering a richer semiotic reading of Old Javanese texts and to religious studies by elucidating fire’s role as both ritual and metaphysical force. Ultimately, this research underscores how ancient symbolic structures continue to inform cultural identity, spiritual practice, and the human search for meaning in contemporary times.